2013
DOI: 10.1118/1.4790689
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the 4D respiratory lung motion by spatiotemporal registration and super‐resolution image reconstruction

Abstract: Purpose:One of the main challenges in lung cancer radiation therapy is how to reduce the treatment margin but accommodate the geometric uncertainty of moving tumor. 4D-CT is able to provide the full range of motion information for the lung and tumor. However, accurate estimation of lung motion with respect to the respiratory phase is difficult due to various challenges in image registration, e.g., motion artifacts and large interslice thickness in 4D-CT. Meanwhile, the temporal coherence across respiration pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…Its application is clinically dependent on a dual-modality imaging system such as SPECT/CT (or PET/CT) where the motion of the SPN could be estimated in respiratory gated CT slices, and applied to correct the SPECT reconstructions [16;17;37]. Currently two separate imaging sessions are necessary with SPECT/CT in order to acquire both the lesion motion and SPECT data.…”
Section: Discussionmentioning
confidence: 99%
“…Its application is clinically dependent on a dual-modality imaging system such as SPECT/CT (or PET/CT) where the motion of the SPN could be estimated in respiratory gated CT slices, and applied to correct the SPECT reconstructions [16;17;37]. Currently two separate imaging sessions are necessary with SPECT/CT in order to acquire both the lesion motion and SPECT data.…”
Section: Discussionmentioning
confidence: 99%
“…We use the target registration errors 39 of the registration results to evaluate the respiratory motion estimation of the lung. The registration results from the methods of Castillo et al, 3 Wu et al, 13 Metz et al, 5 Heinrich et al, 7 and our method on 300 landmark points between the MI phase and ME phase are shown in Table II Table II, the mean and standard deviation of the target registration errors for the 3000 landmark points of ten cases in the DIR-lab dataset are 1.21 and 1.04 mm, respectively. The results of our method are the best for most of the cases with the smallest mean and standard deviation of the target registration errors.…”
Section: A1 Evaluation On the Dir-lab And Popi-model Datasetsmentioning
confidence: 92%
“…In Table III, the results obtained by Metz et al 5 are only available for the POPI-model dataset and for the first five cases of the Dir-lab dataset, and the results obtained by Wu et al 13 are available for the entire DIR-lab dataset. For fair comparison, the results of our method will be compared to the results of Wu et al obtained without super-resolution.…”
Section: A1 Evaluation On the Dir-lab And Popi-model Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation across different phases must be taken into account [14][19]. For example, a spatio-temporal dictionary has been trained to encode the whole dataset which is superior to the spatial dictionary [3][4] because the temporal coherence across respiration phases is usually not guaranteed otherwise [20]. Generally speaking, the dimensionality of this dynamic dictionary is 3-D or higher dimensions, and the tensor notion has been used to deal with multidimensional data as a powerful tool [21]–[24].…”
Section: Introductionmentioning
confidence: 99%